2009
DOI: 10.1055/s-0029-1185685
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Phase II Detoxification Enzyme NQO1 in Hepatocarcinoma Cells by Lignans from the Fruit ofSchisandra chinensisthrough Nuclear Accumulation of Nrf2

Abstract: The upregulation of phase II detoxification genes is believed to play an important role in cancer prevention. The molecular mechanism underlying the changes in gene expression that accompany cancer prevention involves activation of the transcription factor, NF-E2-related factor 2 (Nrf2). In traditional medicine, the fruit of Schisandra chinensis Baill is used as a tonic, an anti-tussive and an anti-aging drug. In the current study, nine lignans were isolated from S. chinensis and tested for their ability to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 16 publications
2
36
0
Order By: Relevance
“…1) were purified as previously described. 20) Fruits of S. chinensis (250 g) were extracted 3 times with MeOH by sonication for 1 h. After filtration, the MeOH extract was evaporated and extracted with n-hexane and CH 2 Cl 2 consecutively. The n-hexane fraction (10 g) was chromatographed on an RP-18 column (4:5 Â 20 cm, 5:5-9:1 MeOH: water, v/v) to yield Fr.…”
Section: Methodsmentioning
confidence: 99%
“…1) were purified as previously described. 20) Fruits of S. chinensis (250 g) were extracted 3 times with MeOH by sonication for 1 h. After filtration, the MeOH extract was evaporated and extracted with n-hexane and CH 2 Cl 2 consecutively. The n-hexane fraction (10 g) was chromatographed on an RP-18 column (4:5 Â 20 cm, 5:5-9:1 MeOH: water, v/v) to yield Fr.…”
Section: Methodsmentioning
confidence: 99%
“…They demonstrated that lipophilic extracts, containing ligustilide, and monooxygenated ligustilide, alkylated some key cysteine residues in the human Keap1 protein, thereby activating the NRF2 gene, and upregulating the transcription of ARE-regulated genes (76). Lee and co-workers also showed that lignans from the fruit of Schisandra chinensis led to a similar endpoint through nuclear accumulation of Nrf2 (77). A wide range of phytochemicals and other putative chemopreventive agents have been found to be anti-mutagens through similar mechanisms (17).…”
Section: Examples Of Mechanisms Of Anti-mutagen Protection Against DImentioning
confidence: 92%
“…2A). 20) Furthermore, YA, YB, and YC showed a relatively high CI arising from low cytotoxicity (IC 50 Ͼ500 mM) and low CD values ( Table 3). The CI was determined by dividing the IC 50 (concentration required to inhibit cell growth by 50%) with the CD value (concentration required to double the QR activity).…”
Section: Increase In Qr Activity Exerted By Youngiasidesmentioning
confidence: 99%